Effect of a toggle switch mutation in TM6 of the human adenosine A(3) receptor on Gi protein-dependent signalling and Gi-independent receptor internalization - Stoddart, Leigh A (Blackwell Publishing Ltd, 2014)
BACKGROUND AND PURPOSE: The highly conserved tryptophan (W6.48) in transmembrane domain 6 of GPCRs has been shown to play a central role in forming an active conformation in response to agonist binding. We set out to characterize the effect of this mutation on the efficacy of two agonists at multiple signalling pathways downstream of the adenosine A(3) receptor. EXPERIMENTAL APPROACH: Residue W6.48 in the human adenosine A(3) receptor fused to yellow fluorescent protein was mutated to phenylalanine and expressed in CHO-K1 cells containing a cAMP response element reporter gene. The effects on agonist-mediated receptor internalization were monitored by automated confocal microscopy and image analysis. Further experiments were carried out to investigate agonist-mediated ERK1/2 phosphorylation, inhibition of [(3)H]-cAMP accumulation and β-arrestin2 binding. KEY RESULTS: NECA was able to stimulate agonist-mediated internalization of the W6.48F mutant receptor, while the agonist HEMADO was inactive. Investigation of other downstream signalling pathways indicated that G-protein coupling was impaired for both agonists tested. Mutation of W6.48F therefore resulted in differential effects on agonist efficacy, and introduced signalling pathway bias for HEMADO at the adenosine A(3) receptor. CONCLUSIONS AND IMPLICATIONS: Investigation of the pharmacology of the W6.48F mutant of the adenosine A(3) receptor confirms that this region is important in forming the active conformation of the receptor for stimulating a number of different signalling pathways and that mutations in this residue can lead to changes in agonist efficacy and signalling bias.